Early result of pediatric shaft femur fractures treated by hip spica cast in children upto 10 years of age - Muzzafar, Khalid; Singh, Rajinder; Bhat, Suhail Ahmad; Haseeb, Muhammad; Ghani, Abdul (International Journal of Research in Medical Sciences, 2017)
Background: Fracture shaft of femur is constitute 1.6% paediatric fractures. Traditionally most femur fractures in children were treated conservatively, however with the coming of new implants, the indications of operating have increased. We believe guidelines based on age are from western literature where children are usually of big frame, our children being of smaller frame, the conservative management by hip spica can be extended to older children. Methods: This study was done to see the results of conservative management of femur fractures in form of hip spica and traction followed by spica in children less than 10 years of age. Patients less than 6 months of age (treated by Pavlik harness), having compound fractures and those with associated injuries were excluded from the study Results: Follow up was done in OPD after 1,4,6,10,12 weeks with check X-rays taken after spica application and at 6, 10 ,12 weeks and at removal of spica cast. All fractures united with average union time of 7.3weeks. At final follow up of 1 year 23 patients had a limb length difference of more than 1cm. average hospital stay was 13.5 days. We had 4 cast complications in form of skin excoriation and superficial skin ulceration in 2 children and broken spica in 2 children. Conclusions: Traction followed by spica cast is safe and effective method of treating fracture of paediatric femur fractures.